Gender and women’s self-employment in the Moroccan context of rural cooperatives - Damou, Sara; Harmaz, Meryem; Hougua, Ben Ahmed; Aftiss, Ahmed (Edelweiss Applied Science and Technology, 2025)
In Morocco, the participation of rural women in socio-economic life is not only a matter of human rights but also a social benefit to be gained through the development of their skills and talents. Cooperatives are recognized and recommended worldwide as a model for supporting women economically and socially, reducing gender inequalities, and fostering local development through their economic contributions. The aim of this study is to examine the effects of women’s cooperatives on rural women’s self-employability and gender inequalities. At the same time, we move beyond a macroeconomic perspective to a social and relational one, through the subjective and concrete experiences of Moroccan women’s cooperatives. To this end, we used a qualitative methodology based on snowball sampling to collect data on the ways and degrees to which members experience an improvement in their employability after joining cooperatives, drawing on the real-life narratives of women from rural backgrounds. The study reveals that cooperatives enable women to create their own employment opportunities, strengthening their economic and social independence and their ability to support themselves and their families. Although cooperatives do not have a direct and immediate effect on gender inequalities, they do at least help to reduce them to some extent. Inequalities remain influenced by cultural legacies and traditional norms in rural areas, which are difficult to change even after women have achieved financial and social independence.